Assessing household food security of rice farmers in Barangay San Jose, Koronadal City, South Cotabato - Acosta, Maria Loren G. (2016)
Household food security requires sufficient home production of food or adequate economic and physical access to food, thus, it is connected to households? income and resources. Food security was assessed at the household level since it is the basic economic unit that determines the consumption of an individual. Small and marginal farmers are said to be at the greater risk of being food insecure because they often have lesser resources and lower income. In particular, the study assessed the level of food security, identified the different factors affecting it, and determined the different coping mechanism used to avert hunger by 153 rice farmer households in an irrigated area in Barangay San Jose, Koronadal City. Household Food Security Access Scale (HFIAS) and Coping Strategies Index (CSI) were used in the study. The variables used in assessing household food security are: socio-demographic profile in terms of age, educational attainment, household size, yield per hectare, income per hectare and coping mechanisms. Results of the study revealed that rice farmers in Barangay San Jose, Koronadal City were mostly food insecure and they are using different coping strategies when they lack resources. Household size and yield per hectare in their rice farming were identified as factors that affect their household food security. Farmers with bigger household size tend to be more food insecure, and improvement in their yield per hectare in rice farming could improve their level of food security.